Greenland, view of Kjerulf Fjord near entrance to Kejser Franz Joseph Fjord - Boyd, Louise Arner, 1887-1972 (1931)
July 31, 1931. Kjerulfs [Kjerulf] Fjord. Outer end. In background; Riddarborgen (Peak) is here seen forming west side of the fjord very near entrance to Kaiser Franz Josef [Kejser Franz Joseph Fjord]. In foreground; S.S. Veslekari anchored close to shore can be seen behind iceberg. Photo taken from motor-boat looking west.